If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(m/2)-(1/m)=(6m+5/12)
We simplify the equation to the form, which is simple to understand
(m/2)-(1/m)=(6m+5/12)
Remove unnecessary parentheses
+ 0.5m-(/m)=(6m + 0.41666666666667)
Remove unnecessary parentheses
+ 0.5m-1m=(6m + 0.41666666666667)
Remove unnecessary parentheses
+ 0.5m-1m=6m + 0.41666666666667
We move all terms containing m to the left and all other terms to the right.
+ 0.5m-1m-6m=0.41666666666667
We simplify left and right side of the equation.
-6.5m=0.41666666666667
We divide both sides of the equation by -6.5 to get m.
m=-0.064102564102564
| X^2+6X=34 | | 15x-75=90 | | Y=(15x+10)(15x-2) | | 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 | | 1.3x+1.6y=.6 | | 15x-150=90 | | -8-2(8n-8)=-6n+8 | | 5x-2x-3=27 | | -76+n=-115 | | 6tx=4+2 | | 5x-6+6/5=14+6/5 | | 3a+8+a-9-2= | | 15=9w | | 10x+34=114 | | (x+2)2=13 | | -13+3x=-52+24 | | 4cos^2(x)+1=3 | | 5x+6+6/5=16+6/5 | | 8p+2=4-10 | | 5x+59=99 | | 3+2*(-x+4)= | | 6x=-4x^2 | | 16x+68=180 | | -6+8k=4(1+4k)-6k | | 7-15t=5s-3 | | 4x+-15=17+-4x | | w*W+16=8w |